Ballistic impact performance of composite laminates based on high‐density polyethylene/montmorillonite nanocomposite and Aramide fiber. Issue 10 (7th August 2021) - Dias, Rafael R.; Zattera, Ademir J.; Pereira, Iaci M.; Soares, Bluma G.
Abstract: Nanostructured thermoplastic consisting of high‐density polyethylene (HDPE) modified with exfoliated montmorillonite (MMT) was successfully used as the matrix for the development of composite for ballistic applications. The effect of HDPE and HDPE/MMT as the matrix on the mechanical and ballistic properties of para‐aramid plain‐woven fabric‐based composites was compared with the commercial composite constituted by polyvinyl‐butyral–phenolic resin as the matrix. The dynamic compressive tests using split Hopkinson pressure bar equipment revealed a remarkable increase of maximum compression strength, outstanding dynamic compressive response, and superior tenacity for the composite containing HDPE/MMT as the matrix. Moreover, the ballistic limit of the HDPE/MMT‐based composite was the highest one. Mechanical failures indicated that this matrix was able to interact with a greater fiber volume and was responsible for improving the ballistic impact energy absorption. Thus, the use of MMT in thermoplastic matrix may be considered a promising ballistic solution due to the possibility of combining lightweight and ballistic resistance. Abstract :